(untitled) (Colloquia Comparativa Litterarum, 2025)
Bulgarian modernism, edited by Stefana Roussenova, translated by Julia Stefanova and Stefana Roussenova, Polis, Sofia, 2017. Authors: Svetlozar Igov, Madeleine Danova, Svetlana Stoicheva, Bilyana Borisova, Magdalena Panayotova, Dina Mantcheva, Elizaria Ruskova, Giuseppe del’ Agata, Vladimir Yanev, Julia Stefanova, Chavdar Mutafov, Juliana Alexieva. Appendix: poetry by Pencho Slaveikov, Peyo Yavorov, Dimcho Debelyanov, Geo Milev, Nikola Vaptsarov, Atanas Dalchev.